Meningkatkan Keefektifan Organisasi Karang Taruna di Tengah Wabah Covid-19 Melalui Pemahaman Kecerdasan Emosi - Lindiawatie Muhamad; Dhona Shahreza (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
The existence of youth organizations in the midst of the Covid-19 outbreak is urgently needed to partner with the government and related agencies as volunteers and spearheads in dealing social problems that arise due to the impact of the Covid-19 outbreak. However, the fact is that the credibility of the organization is looked down upon by the public. Based on that fact, this community service is carried out, namely to increase the effectiveness of the organization in the midst of the Covid-19 outbreak through understanding emotional intelligence. Method of delivery by counseling and interactive discussions through online media. The result achieved is that the presentation of emotional intelligence create awareness in member and committee organization to take action but does not understand the technical in the field. Thus understanding of emotional intelligence is basically able to encourage organizational effectiveness with the motivation to act.